Research on Improving the Working Efficiency of the Group Installation of Outdoor Units of the VRF Air Conditioning System - Nguyen , Văn Tâm; Tran, Văn Hưng; Nguyen, Thị Minh Trinh; Nguyen , Minh Phú; Nguyen, Văn Hạp (Journal of Technical Education Science, 2022)
The Variable Refrigerant Flow (VRF) central air-conditioning system is widely used in commercial buildings because of its outstanding advantages, especially the building which has a significant daily variation in cooling load. When the number of outdoor units in group installation increases, the coefficient of performance of the VRF system decreases due to the recirculation phenomenon of hot exhaust air from outdoor units. In this study, 3D models of outdoor unit group installation on rooftop were built and studied through Computational Fluid Dynamics (CFD) simulation using Ansys Fluent. The simulation results show that the air temperature entering outdoor units in the central region of the group is higher than that in the outer region. When air guides are installed, the average temperature of the air entering the outdoor units is reduced by 2.3%, while the maximum temperature decreased by 4%. This result can be used as the guidance for the optimization design of group installation for VRF condensers